An Efficient Reliable Communication Scheme in Wireless Sensor Networks Using Linear Network Coding - Jin Wang; Xiumin Wang; Shukui Zhang; Yanqin Zhu; Juncheng Jia (International Journal of Distributed Sensor Networks)
We address the modeling and design of linear network coding (LNC) for reliable communication against multiple failures in wireless sensor networks (WSNs). To fulfill the objective, we design a deterministic LNC scheme RDLC based on the average number of path failures simultaneously happening in the network other than the maximum number of path failures. The scheme can significantly improve the network throughput comparing with the traditional approaches. In our study, we also investigate the potential of random linear code RRLC for providing reliable communication in WSNs and prove the low bound of the probability that the RRLC can provide the reliable communication. Finally, extensive simulation experiments have been conducted, and the results demonstrate the effectiveness of the proposed LNC schemes.